Using “Pub Quiz” to promote participation and active learning in prospective teachers - Gull Fariha,; Shaheen Faiza,; Rana Rizwan Akram, (penerbit ukm, 2015)
It has become an established fact that wheneverr students and teachers are involved equally for learning purpose, the use of effective and innovative teaching strategies serve the purpose at its optimal level. Both active learning and classroom participation have been found influential by increasing classroom performance of the students. Having knowledge about the use of multiple teaching strategies and knowing ways to modify applicable strategies in attaining teaching objectives are sensitive, yet crucial to apply in classrooms especially when it is subjected to prospective teachers. The current study was aimed to explore the effect of pub quiz activities on active learning, classroom participation and academic performance of prospective teachers that emphasized the idea of integrating activities in teacher training programs. Sample of the study comprised 22 prospective teachers enrolled in Science course of one year degree program at a public teacher training institute. It was an experimental study that allowed integrating the use of multiple activities during eight weeks of running semester. A five point Likert type scale followed by an open ended questionnaire was used to measure the level of participation and active learning of prospective teachers; whereas their academic performance was measured through taking a test. Data was analyzed by using descriptive statistics and thematic analysis. The results supported the assumption of the study that integration of planned and relevant activities into teaching are not only helpful in pursuit of positively affecting the active learning, classroom participation and academic performance of prospective teachers but also helpfull in breaking the monotony of conventional ways of teaching and learning. The study recommended that adopting flexible use of activities accelerates learning process by ensuring active participation and learning on the part of students.